Ore-forming processes within granitic pegmatites - London, David (Ore geology reviews, 2018)
[Display omitted] •Granitic pegmatites result from extended fractional crystallization of large granitic plutons.•Liquidus undercooling is the single most important factor in forming granitic pegmatites.•Experiments have replications pegmatitic zonation and texures. Pegmatites are texturally complex igneous rocks marked by some combination of coarse but variable crystal size, mineralogical zonation, prominent anisotropy of crystal orientations from the margins inward, and skeletal, radial, and graphic intergrowth habits of crystals. The vast majority of pegmatites are granitic in composition, and this article pertains to these rocks. Pegmatites occur as segregations near the roofward contact of their source pluton, as dike swarms emanating from their plutons into the surrounding igneous and metamorphic rocks, and as planar to lenticular intrusive bodies whose sources are not exposed. Granitic pegmatites are important economic sources of industrial minerals (feldspars, quartz, spodumene, petalite) for glass, ceramic, and electronic applications, of a wide variety of lithiophile rare elements (Li, Cs, Be, Nb, Ta, Sn, etc.) that are incompatible in the predominant rock-forming minerals of granites, and of colored gemstones and valuable mineral specimens (of beryl, tourmaline, topaz, etc.). All of the salient features of pegmatites – their mineral habits, distinctive rock fabrics, and spatial zonation of mineral assemblages, including monominerallic bodies – arise from appreciable liquidus undercooling (by ∼200° ± 50 °C) of viscous granitic liquids prior to the onset of crystallization. The ore-forming processes within granitic pegmatites are entirely igneous as a result of extended fractional crystallization of large granitic plutons, and in response to crystallization at a highly supersaturated state of the melt in pegmatite-forming bodies. Constitutional zone refining, wherein a flux-enriched boundary layer of liquid develops adjacent to the crystallization front and eventually becomes the last liquid in the pegmatite body, appears to be the most likely mechanism to account for increasing crystal dimensions (and consequently decreasing numbers of crystals) and late-stage bodies of rare-metal ores that are the hallmarks of the class of rare-element pegmatites. The most prevalent manifestation of mineralogical zonation, in which plagioclase (initially An10-20) dominates the outer zones, K-feldspar follows in intermediate zones, and quartz is concentrated in the last-formed core units, can be rationalized by the relative magnitudes of the Gibbs Free Energies of crystallization of feldspars versus quartz and of plagioclase versus K-feldspar solid solutions. Importantly, the sequential crystallization of feldspars and quartz at a highly undercooled state of melt is predicted on thermodynamic grounds even for melts of eutectic composition. Highly contrasting diffusivities of alkalis versus high field-strength elements (HFSE) in pegmatite-forming liquids lead to long-range and short-range effects of element migration or concentration: low diffusivities of HFSE promote boundary-layer pile-up and local, episodic saturation of minerals at the crystallization front. Long-range diffusivities of alkalis give rise to the spatial segregation of plagioclase and K-feldspar along opposing margins of dikes, and of isolated but gigantic crystals of rare minerals such as pollucite. Exploration for pegmatites as sources of economic commodities relies entirely on surface discoveries. However, the regional zonation of pegmatite bodies, and the chemistry of metasomatic alteration in the host rocks to rare-element pegmatites, give some indications of the probability of finding deposits of ceramic materials, rare-metal ores, and even gemstones.